Evaluation of dental pulp stem cells’ growth phases on their differentiation towards dopaminergic-like cells / Naresh Waran Gnanasegaran - Naresh Waran , Gnanasegaran (2017)
Parkinson’s disease (PD) is a debilitating, incurable neurodegenerative movement disorder that is defined by the gradual emergence of motor as well as non-motor symptoms and affects approximately 3% of people over sixty-five years old. The two pathological hallmarks of PD include progressive deterioration of dopaminergic (DA-ergic) neurons within the substantia nigra (SN) and the widespread distribution of Lewy bodies. As a result, a large numbers of DA-ergic neurons are needed to replace the depleted neurons to revert the symptoms presented by PD patients. Cell replacement therapy (CRT) has been suggested to be the future possible treatment modality since current treatments were deemed ineffective in managing symptoms of PD. Among the widely described cell source, dental pulp stem cells from extracted deciduous tooth (SHEDs) has been regarded as the optimal cell source owing to the fact that they are originate from neural crest and display high neuronal differentiation capacity, migratory activity rate and regenerative potential. Furthermore, the inherent characteristics of cells such as growth phase are hypothesized to play significant roles in determining their regenerative potential. In this study, both in vitro and in vivo capabilities of SHEDs at selected growth phases were investigated, firstly differentiation towards DA-ergic-like cells, followed by determination of respective gene as well as protein expression. It was demonstrated that neuronal markers such as nestin and β-tubulin-III as well as matured DA-ergic markers like tyrosine hydroxylase (TH) were highly up-regulated in SHEDs-Day 7 which was also reflected in their functional behaviour (p<0.05). The differential output (i.e differentiation capacity and functionality) obtained from various growth phases were believed to be directly involved with their cell cycle profile. Further, the immunomodulatory behaviour of SHEDs was also evaluated in a microenvironment depicting neuro-inflammation of typical PD scenarios. The cells were shown to significantly alter the profile of inflammatory cytokines secreted such as interleukins-1α, 6, 8, interferon-gamma, as well as tumor necrosis factor-α, but were unable to regulate the levels of nitric oxide and reactive oxygen species (p<0.05). This findings indicate that they exhibit some degree of neuro-protective ability over damaged neurons. Finally, SHEDs were evaluated for their homing capacity as well as their regenerative behaviour when they were transplanted via intrathecal in a MPTP-induced mice model. Behavioural assessments were measured from the perspective of sensorimotor as well as olfactory functions. Our findings revealed that PD-induced mice, transplanted with SHEDs displayed improved behavioural changes (approximately 60%) as early as week 8 post-transplantation (p<0.05). The same pattern was also observed in the immunostaining of TH, DA transporter and DA decarboxylase in SN as well as striatum of their brain. In addition, immunohistochemistry analysis revealed homing capacity of SHEDs at areas related to SN which was identified from the expression of matured DA marker, TH. In conclusion, this study has highlighted the regenerative capacity of SHEDs from the perspective of differential growth phases. It is suggested that the growth phase of cells to be considered as one of many important parameter when designing personalised cell replacement therapies in the future.